Manual de gestión de crédito y cobranza para la caja de ahorro confianza al desarrollo comunitario. - Túquerres, Leslie L. (2023)
Associative or solidarity entities, community banks and banks, and savings banks, are formed by the will of its partners, within the limits and forms established by the Financial Policy and Regulation Board. These entities have their own structure government, administration, representation, self-control and accountability. They form with the economic contributions of its partners in the form of savings, without being able to raise funds from third parties. They can grant credits exclusively to their partners, following the regulations issued by the Financial Policy and Regulation Board. They can also receive reimbursable or non-reimbursable financing for its development and strengthening, granted by entities of the national financial system, support entities and cooperation, both national and international (Superintendency of Economy Popular and Solidarity, 2021).